Modern liberty and the limits of government - "Fried, Charles" (New York, 2007)
In this impassioned defense of liberty, renowned Harvard law professor Charles Fried argues that the seemingly unimpeachable goals of equality and community are often the most potent rivals of freedom. Declared a (3z(Bspirited, sophisticated manifesto(3y (Bby the New York Times Book Review, Modern Liberty demonstrates how the dense tangle of government regulations both supports and threatens our personal liberties. Armed with Fried$1 (Bs insights, readers will be better able to defend themselves against those on both the left and the right who would, even with the best intentions, restrict their liberty.s
Keywords: Liberty